Molecular Detection Of Somatic Embryogenesis in Drosera tokaiensis - Vimukthi, Bandara Jaysundara (2017)
Drosera tokaiensis is a carnivorous plant with many potential uses in the fields of medicine. Hence potential demand for D. tokaiensis may cause endangerment to the species. A rapid need for plant production which can be acheived by somatic embryogenesis (SE) which produces higher propagates with less variation compared to to organogenesis. Detection of SE is important because it is similar in structure to organogenesis and callogenesis. SE detection by observation of cellular structures is time consuming. Thus, a molecular detection of SE induction using elongation factor a(EFI) and somatic embroygenesis recptor-like kinase (DERKI1) was proposed using quantitative polymerase chain reaction (qPCR) approach. RNA samples were available from D. tokaiensis leaves induced for SE using thiadiazuron from day (D)-0 to D28, RNA integrity of these samples were confirmed by agarose gel electrophoresis. Then cDNA was synthesised and qPCR was carried out using specific primers designed for SERI1 and EF1 along with house-keeping genes, ACT and GAPDH. The experimentwas relaible with PCR efficiently measured, and amplification specificity proven by database comparison and local alingment to known sequence. EF1, ACT and GAPDH could be accurately quantified where R-squared value of the generated standard curve was more than 0.99. Expression of EFI and SERK1, after normalization with ACT and GAPDH as references, was shown to be upregulated during SE induction stages of SE induction and could be used as genetic makers for detection of SE induction for production lines and also tissue culture experiments involving SE induction